Meningkatkan Pra-Sarana Informasi Di Kampung Holmafen Distrik Sarmi Timur - Henderina Morin; Alienra Davry Nanda Kadun MT; Rahmat Nurjaman (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
Distribution of information has an integral role in village governance. The village government needs to prioritize information services and management to fulfill the ideas of an informative village. This community service takes place in Holmafen village, East Sarmi district, Sarmi regency. The purpose of this service is to the improve information infrastructure in Holmafen. Holmafen is one of the villages in the East Sarmi district which has the potential to be developed, one of the reasons is due to the tourism potential. The method used in this community service is by making physical infrastructure in the form of village information boards (village and Bamuskam nameplates, village monographs - programs, and village organization boards). In conclusion, this service has helped the community and the village government of Holmafen in providing information infrastructure.